Real-World Effectiveness of Primary Series and Booster Doses of Inactivated Coronavirus Disease 2019 Vaccine Against Omicron BA.2 Variant Infection in China: A Retrospective Cohort Study - Tang, Lin; Wang, Fu-Zhen; Rodewald, Lance E; Wang, Xuan-Yi; Liu, Si-Yu; Liu, Qian-Qian; Wang, Xiao-Qi; Wu, Dan; Li, Ming-Shuang; Zhang, Qian; Shao, Yi-Ming; Huang, Li-Fang; et al. (The Journal of infectious diseases, 2023)
Abstract Background China has been using inactivated coronavirus disease 2019 (COVID-19) vaccines as primary series and booster doses to protect the population from severe to fatal COVID-19. We evaluated primary and booster vaccine effectiveness (VE) against Omicron BA.2 infection outcomes. Methods This was a 13-province retrospective cohort study of quarantined close contacts of BA.2-infected individuals. Outcomes were BA.2 infection, COVID-19 pneumonia or worse, and severe/critical COVID-19. Absolute VE was estimated by comparison with an unvaccinated group. Results There were 289 427 close contacts ≥3 years old exposed to Omicron BA.2 cases; 31 831 turned nucleic acid amplification test–positive during quarantine, 97.2% with mild or asymptomatic infection, 2.6% with COVID-19 pneumonia, and 0.15% with severe/critical COVID-19. None died. Adjusted VE (aVE) against any infection was 17% for primary series and 22% when boosted. Primary series aVE in adults >18 years was 66% against COVID-19 pneumonia or worse and 91% against severe/critical COVID-19. Booster dose aVE was 74% against pneumonia or worse, and 93% against severe/critical COVID-19. Conclusions Inactivated COVID-19 vaccines provided modest protection from infection, very good protection against pneumonia, and excellent protection against severe/critical COVID-19. Booster doses are necessary to provide strongest protection. China-produced inactivated COVID-19 absolute vaccine effectiveness (VE) levels against Omicron BA.2 infection, pneumonia or worse, and severe COVID-19 were 17%, 66%, and 91%; boosted VEs were 22%, 74%, and 93%. Inactivated vaccines were highly effective against severe COVID-19 in China's then infection-naive population.